Totalitarian capitalism and beyond - Liodakis, G. (Ashgate Pub., 2010)
Anchored in contemporary debates on capitalism and political economy, this study reconsiders the major trends which are shaping a new stage of capitalism. It constructs a politico-economic approach on contemporary capitalism from within a classical Marxist framework of political economy.